Influences of Maternal Factors Over Offspring Allergies and the Application for Food Allergy - Fujimura, Takashi; Lum, Shelly Zing Chin; Nagata, Yuka; Kawamoto, Seiji; Oyoshi, Michiko K. (Frontiers in Immunology, 2019)
The prevalence of food allergy has been steadily rising worldwide with the highest incidence noted among younger children, and increasingly recognized as a growing public concern. Allergic reactions to foods often occur on the first known ingestion, suggesting that exposure of offspring to food allergens may occur in utero and/or through breast milk. This creates a milieu that shapes the neonatal immune response to these allergens. However, the effects of maternal allergen exposure and maternal sensitization with allergens on development of allergies in offspring remain controversial. This review discusses recent advances from human data in our understanding of how maternal factors, namely, food allergens, allergen-specific immunoglobulins, cytokines, genetics, and environmental factors transferred during pregnancy or breastfeeding influence offspring allergies and how such effects may be applicable to food allergy. Based on information obtained from mouse models of asthma and food allergy, the review also dissects the mechanisms by which maternal factors, including the impact of immune complexes, transforming growth factor-β, vitamin A, and regulatory T-cell responses, contribute to the induction of neonatal tolerance versus development of allergic responses to maternally transferred allergens.